PEMUTUSAN KONTRAK AKIBAT WANPRESTASI PADA KONTRAK KERJA KONSTRUKSI DRAINASE DI TANJUNG GUSTA KABUPATEN DELI SERDANG (STUDI KASUS ATAS KONTRAK NOMOR 600/DR.23/SP/ DCKP/ DS/2015) - WINNI UTARI (PREMISE LAW JURNAL, 2017)
The role and liability of the Notary are to ensure whether the call for the RUPS (General Meeting of the Shareholders) is made which is in line with Article 82 of the Law on Limited Company, includes the agenda of the RUPS, ensures that the stakeholders attending the meeting matches the most recent list of the shareholders, makes minutes of the meeting and is responsible for the application of the addendum of the article of association to the Minister. The obstructions are caused by some factors such as the limited company incomplete data, management, application cost, unregistered addendum of the article of association, unsuitable data, Notary’s negligence and weakness in the laws. Moreover, the legal consequences to the Limited Company for its late application of the addendum of the articles of association to the Minister or that the addendum has not been recorded in the Limited Company List run by the Ministry of Law and Human Rights is that the Ministry can refuse all applications for then addendum. Consequently, it will cause difficulty for the limited company when it needs some credit from the bank because the bank will require a memorandum of association or its last addendum of articles of association. Keywords: Limited Company, Notary, Application of Addendum of Articles of Association to the Minister.